Fibrin Hydrogel Aided Cardiac Progenitor Cell Delivery Enhances Regenerative Tendency in Myocardial Infarct Model - S, Subha; Shenoy, Sachin J; Anil, Arya; A, Sabareeswaran; AN, Deepthi; Krishnan, Lissy K (Archives of Clinical and Biomedical Research, 2020)
Attempts to regenerate myocardial infarct (MI) using stem cells have been achieving random success rates. This study considered delivering cardiac progenitors (rCPs), developed from rat adipose-derived mesenchymal stem cells (rADMSCs), into rat MI tissue. The study aimed to employ fibrin-based insoluble matrix as a niche for in vitro differentiation of rADMSCs to rCPs and specific composition of fibrin hydrogel to deliver the cells into MI tissue. PKH26 tracker dye labelled-rCPs/rADMSCs suspended in fibrinogen/thrombin was injected to peri-infarct zone in rat heart created by coronary artery ligation. The MI tissues were harvested after 28d, imaged to locate transplanted cells, and analyzed to detect markers of differentiation, angiogenesis, and immune response. Co-localization of Connexin 43/TroponinT with PKH26 indicated differentiation of transplanted progenitors into cardiomyocyte like cells. Additionally, the presence of CD31+ve cells, fewer CD68+ve cells, and reduced collagen deposition are appreciable in tissues transplanted with rCP in fibrin, as compared to those that received rADMSC. The results obtained indicate that fibrin acts as a favorable niche for in vitro priming of rADMSCs into transplantable lineagecommitted rCPs. The in situ clottable fibrin aided the retention and differentiation of transplanted rCPs into cardiomyocytes. Also by 28d, the tissues showed better angiogenic/ immunomodulatory effects and reduced the calcification tendency.